Pilomatrixoma in Periocular Tissues: A Case Report from Bangladesh - Islam, Md. Nazmul; Lodh, Dipankar; Siddiqui, Mohammad Mamun; Mannan, Mahedi; Khan, AF Mohiuddin (Journal of Science Foundation, 2016)
Benign calcifying epithelioma of Malherbe or pilomatrixoma or pilomatricoma is less common lesion of the periocular tissues arising from the matrix cells at the base of the hair. In the periocular area, it usually arises from the lids and eyebrows. Pilomatrixoma has certain characteristic clinical and histopathological features, but since it is not commonly suspected preoperatively, certain distinctive clinical features of tumour should suggest clinical diagnosis followed by histopathological confirmation. Journal of Science Foundation, 2015;13(1):21-24 DOI: http://dx.doi.org/10.3329/jsf.v13i1.27830